Underperception of Naps in Older Adults Referred for a Sleep Assessment: An Insomnia Trait and a Cognitive Problem?. Issue 10 (29th September 2015) - Nguyen‐Michel, Vi‐Huong; Lévy, Pierre‐P; Pallanca, Olivier; Kinugawa, Kiyoka; Banica‐Wolters, Raluca; Sebban, Claude; Mariani, Jean; Fournier, Emmanuel; Arnulf, Isabelle
<x xml:space="preserve">Abstract</x> Objectives To examine the frequency and determinants of underperception of naps in older adults referred for a sleep assessment. Design Prospective study. Setting Outpatient geriatric sleep clinic. Participants Individuals aged 60 and older referred for insomnia complaints or suspected sleep apnea (N = 135). Measurements Tests included clinical interview, sleepiness scale, anxiety and depression scale, Insomnia Severity Index (ISI), Mini‐Mental State Examination (MMSE), and overnight polysomnography, followed by multiple sleep latency tests. At the end of each of four nap opportunities, participants answered whether they had slept during the test. Nap underperception was defined as two or more unperceived naps. Results Of the 105 participants who napped at least twice, 42 (40%) did not perceive at least two naps. These participants had lower MMSE scores (P = .01) and were more likely to be taking benzodiazepines (P = .008) than the 63 participants who did not underperceive their naps but had similar demographic characteristics, sleep diagnoses, depression and anxiety scores, and polysomnography measures. Both groups had similarly short mean daytime sleep latencies (9.7 ± 4.5 minutes and 9.8 ± 3.7 minutes), but participants who underperceived their naps scored lower on the Epworth Sleepiness Scale (5.6 ± 4.0, vs 9.6 ± 4.8, P < .001). An ISI of 11 or greater, a MMSE score of 26 or less, and a sleepiness score of 8 or less were each independently associated with underperception of naps. The combination of these three factors yielded a positive predictive value of 93% and a negative predictive value of 71% for nap underperception. Conclusion Older adults referred for sleep consultation with cognitive impairment and greater insomnia symptoms frequently underperceive naps, leading them to underestimate their level of sleepiness. In such cases, objective measures of daytime sleepiness would be better than the Epworth Sleepiness Scale.